2018
DOI: 10.12659/msm.909633
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-365 Inhibits Cell Growth and Promotes Apoptosis in Melanoma by Targeting BCL2 and Cyclin D1 (CCND1)

Abstract: BackgroundMicroRNA-365 (miR-365) is involved in the development of a variety of cancers. However, it remains largely unknown if and how miRNAs-365 plays a role in melanoma development.Material/MethodsIn this study, we overexpressed miR-365 in melanoma cell lines A375 and A2058, via transfection of miR-365 mimics oligos. We then investigated alterations in a series of cancer-related phenotypes, including cell viability, cell cycle, apoptosis, colony formation, and migration and invasion capacities. We also vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Given that the MAPK/ STAT3/cyclin D1 (encoded by the human CCND1) and PI3K signalling pathways are responsible for cell proliferation, differentiation and survival, [16][17][18][19][20] we then explained the role of MAPK/STAT3, cyclin D1 and PI3K/AKT signalling pathways in rhMYDGF-mediated HCAEC proliferation. Subsequently, we tested the bioactivity and potential mechanism of rhMYDGF in HCAECs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the MAPK/ STAT3/cyclin D1 (encoded by the human CCND1) and PI3K signalling pathways are responsible for cell proliferation, differentiation and survival, [16][17][18][19][20] we then explained the role of MAPK/STAT3, cyclin D1 and PI3K/AKT signalling pathways in rhMYDGF-mediated HCAEC proliferation. Subsequently, we tested the bioactivity and potential mechanism of rhMYDGF in HCAECs.…”
mentioning
confidence: 99%
“…Subsequently, we tested the bioactivity and potential mechanism of rhMYDGF in HCAECs. Given that the MAPK/ STAT3/cyclin D1 (encoded by the human CCND1) and PI3K signalling pathways are responsible for cell proliferation, differentiation and survival, [16][17][18][19][20] we then explained the role of MAPK/STAT3, cyclin D1 and PI3K/AKT signalling pathways in rhMYDGF-mediated HCAEC proliferation. Taken together, this study demonstrates a more economical method to produce high biologically active form of rhMYDGF, and that would be beneficial for the clinical transformation of MYDGF as a promising therapeutic molecule for the future treatment of patients with ischaemia-reperfusion injury.…”
mentioning
confidence: 99%
“…In several studies, BCL2 has been reported to act as a target gene of multiple miRNAs, including miR‐153, miR‐136 and miR‐365 . BCL2 has also been elucidated to be a target gene of miR‐15b in condylar hyperplasia and liver cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, miR-652-5p targeted VEGFA to suppress esophageal squamous cell carcinoma cell proliferation and metastasis [21]. On the other hand, miR-365 was found to compromised the migration and invasion, whereas enhanced apoptosis in melanoma cell lines, which was at least partially due to downregulation of the oncogene Bcl-2 [22]. miR-1290 accelerated asiatic acid-induced apoptosis through decreasing the protein expression of Bcl-2 [23].…”
Section: Discussionmentioning
confidence: 99%